1993
DOI: 10.1136/jech.47.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and causes of mortality differences between married and unmarried men.

Abstract: Study objective-To determine the effect of marital status on mortality for men. In particular, to examine whether subgroups of unmarried men (widowed, single, and divorced/separated men) have a similar mortality to married men. Design-Cohort study Setting-Whitehall civil on relatively small cohorts and are therefore unable to examine cause-specific mortality in any detail.7-9 " Attention has mainly been paid to mortality in widowers compared with married men10 13 14 or has focused on the mortality of married… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(115 citation statements)
references
References 18 publications
10
102
1
2
Order By: Relevance
“…This involved the completion of a study questionnaire and participation in a medical examination, both of which have been described in detail elsewhere. 8 In brief, the questionnaire included enquiries regarding civil service employment grade (an indicator of socio-economic position), 12 smoking habits, 13 intermittent claudication, 14 angina, 15,16 chronic bronchitis, 17 marital status, 18 physical activity, 19 unexplained weight loss in the preceding year and the use of drug therapy for heart problem or high blood pressure. 8 Forced expiratory volume in one second (FEV 1 ) adjusted for height, 20 ischaemia, 21 fasting plasma cholesterol, 22 postchallenge 2-h blood glucose, 23 blood pressure, 24 and triceps skinfold thickness 8 were determined using standardised protocols.…”
Section: Methodsmentioning
confidence: 99%
“…This involved the completion of a study questionnaire and participation in a medical examination, both of which have been described in detail elsewhere. 8 In brief, the questionnaire included enquiries regarding civil service employment grade (an indicator of socio-economic position), 12 smoking habits, 13 intermittent claudication, 14 angina, 15,16 chronic bronchitis, 17 marital status, 18 physical activity, 19 unexplained weight loss in the preceding year and the use of drug therapy for heart problem or high blood pressure. 8 Forced expiratory volume in one second (FEV 1 ) adjusted for height, 20 ischaemia, 21 fasting plasma cholesterol, 22 postchallenge 2-h blood glucose, 23 blood pressure, 24 and triceps skinfold thickness 8 were determined using standardised protocols.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Although many community resources and family members can serve important caregiving roles, the presence of a dedicated spouse may be the most important component of strong social support. Not surprisingly, therefore, most studies have supported the hypothesis that all-cause mortality, cancer-specific mortality, and quality of life are better in married than unmarried cancer patients across many different tumor types, [15][16][17][18][19][20][21][22][23] including primary brain tumors. [24][25][26] This information is important for counseling patients, marshalling resources, and designing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Gliksman et al showed that Australian men aged ≥65 yr who had never married had low average HDL-cholesterol, and that those living alone had high average SBP 6) . However, Kumlin et al 8) and Ben-Shlomo et al 11) in a study of French, Swedish and English workplaces found that CVD risk factors did not differ between married men and those who had never married. We found here, that Japanese married men had fewer CVD risk factors and less clustering of multiple risk factors than those who had never married.…”
Section: Discussionmentioning
confidence: 99%